Extent of Implementation of Conditional Cash Transfer (CCT) Program in a Local Government Unit in Southern Philippines: Basis for Intervention Strategies - Ryan Agregado James; Novelyn Patalita; June Sellar Elton; Christine Tenorio (SHS Web of Conferences)
This study focused on the extent of the Conditional Cash Transfer program implementation in a local government unit in Southern Philippines and the adherence of the Department of Social Welfare and Development (DSWD). The research examined how the agency and the personnel follow guidelines in beneficiary selection, compliance, monitoring, and feedback mechanisms. The study was anchored on Republic Act 11310, the Pantawid Pamilyang Pilipino Program (4Ps) Law, and its Implementing Rules and Regulations (IRR). The Data were collected through a self-made survey instrument focusing on the personnel of the 4Ps employees as the research participants. A quantitative research design was employed. The findings suggest that the program is well implemented. It may be that the DWSD personnel are adhering to the IRR of the 4Ps law. However, challenges were identified, including reliance on manual monitoring, inter-agency cooperation issues, and cultural, social, and educational factors affecting beneficiary compliance and data accuracy. Based on these findings, the researchers proposed intervention strategies to improve beneficiary lives and enhance program operations for DSWD personnel and 4Ps beneficiaries.